A new optical and nuclear dual-labeled imaging agent targeting interleukin 11 receptor alpha-chain - Wang, Wei (2007)
Optical imaging has great potential for studying molecular recognitions both in vivo and in vitro, yet nuclear imaging is the most effective clinical molecular imaging modality. The combination of optical and nuclear imaging modalities may provide complementary information for improving diagnosis and management of diseases. In this study we developed an optical and nuclear dual-labeled imaging agent, 111In-DTPA-Bz-NH-SA-K(IR-783-S-Ph-CO)-c(CGRRAGGSC)NH2, called DLIA-IL11Rα. 111In-DTPA-Bz-NH-SA is the radiotracer moiety; a near-infrared dye IR-783-S-Ph-COOH serves as the fluorescent emitter; and the cyclic peptide c(CGRRAGGSC), which is known to target interleukin 11 receptor alpha-chain (IL-11Rα), delivers the desired imaging agent to its target. Experiments revealed that the cyclic peptide c(CGRRAGGSC) continued to possess the targeting capability to IL-11Rα after the conjugation of the optical and nuclear tracers. Furthermore, the presence of the metal isotope chelator did not cause quenching of fluorescence emission. The cross validation and direct comparison of optical and nuclear imaging of a tumor was achieved using a single injection, and the preliminary results show the conjugate has tumor targeting capabilities in vivo.